2021
DOI: 10.3389/fonc.2021.631703
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal MicroRNAs Mediating Crosstalk Between Cancer Cells With Cancer-Associated Fibroblasts and Tumor-Associated Macrophages in the Tumor Microenvironment

Abstract: Exosomes are small extracellular vesicles containing diverse bioactive molecules. They play essential roles in mediating bidirectional interplay between cancer and stromal cells. Specific elements are selected into different types of exosomes via various mechanisms, including microRNAs (miRNAs), a subset of non-coding RNA that could epigenetically reprogram cells and modulate their activities. Cancer-associated fibroblasts (CAFs) and tumor-associated macrophages (TAMs) are two major types of stromal cells inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 117 publications
0
25
0
Order By: Relevance
“…Exosomes (30–150 nm) are considered as messengers between cells, carrying a large number of macromolecules, including proteins, mRNAs, lipids, and miRNAs, which constitutes an important part of the tumor immune microenvironment ( Wen et al, 2016 ; Bach et al, 2017 ; Ruivo et al, 2017 ; Su et al, 2021 ). Exosomes are nanoscale membranous vesicles secreted from intracellular multivesicular bodies (MVBs) or late endosomes into the extracellular space through extracellular action ( Su et al, 2021 ). CD81, CD63, and TSG101 have become the most commonly used exosomal labeling proteins ( Pegtel and Gould, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exosomes (30–150 nm) are considered as messengers between cells, carrying a large number of macromolecules, including proteins, mRNAs, lipids, and miRNAs, which constitutes an important part of the tumor immune microenvironment ( Wen et al, 2016 ; Bach et al, 2017 ; Ruivo et al, 2017 ; Su et al, 2021 ). Exosomes are nanoscale membranous vesicles secreted from intracellular multivesicular bodies (MVBs) or late endosomes into the extracellular space through extracellular action ( Su et al, 2021 ). CD81, CD63, and TSG101 have become the most commonly used exosomal labeling proteins ( Pegtel and Gould, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The barrier to successful cancer immunotherapy is the capability of tumors to escape from the host’s immune system ( Whiteside et al, 2011 ). Exosomes, small membranous sacs of endocytic origin (30–150 nm), are considered as intercellular messengers that can carry a large number of macromolecular cargos, including proteins, mRNA, lipids, and miRNA ( Wen et al, 2016 ; Bach et al, 2017 ; Ruivo et al, 2017 ; Su et al, 2021 ). Studies have found that exosomes derived from tumors carry immunosuppressive proteins, including PD-1, CTLA-4, FasL, TRAIL, CD39, and CD73, which induce apoptosis and depletion of T lymphocytes to achieve tumor immune escape ( Whiteside, 2013 ; Ukrainskaya et al, 2019 ; Benecke et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Tumor cells are well known to utilize exosomes to change the functions of other cells in the tumor microenvironment (119). In recent years, CAFs were also shown to take part in exosome mediated communications (120). CAF derived vesicles are able to promote the migration and invasion of cancer cells (121,122).…”
Section: The Role Of Cafs On Tumor Progressionmentioning
confidence: 99%
“…183,184 These purification methods cannot easily distinguish exosomes from nonvesicular compartments, which may affect the subsequent experiment of exosomal miRNAs in vivo and in vitro. Second, due to the low abundance of the exosomal miRNAs content in patients' serum, 185 there is lack of high-efficiency method to collect exosomes in clinical application, which restricts the potential clinically relevant application of exosomal miRNAs as diagnostic and therapeutic markers. Third, exosomal miRNAs need to be further investigated to determine whether they are specifically related to one or more diseases, and to explore the underlying molecular mechanisms of exosomal miRNAs in diseases.…”
Section: Opportunities and Challenges Of Exosomal Mirnas In Dmmentioning
confidence: 99%